The Sudden Death of the Nearest Quasar - Schawinski, K; Evans, D; Virani, S; Urry, C; Keel, W; Natarajan, P; Lintott, C; Manning, A; Coppi, P; Kaviraj, S; Bamford, S; Jozsa, G; et al. (2010)
Galaxy formation is significantly modulated by energy output from supermassive black holes at the centers of galaxies which grow in highly efficient luminous quasar phases. The timescale on which black holes transition into and out of such phases is, however, unknown. We present the first measurement of the shutdown timescale for an individual quasar using X-ray observations of the nearby galaxy IC 2497, which hosted a luminous quasar no more than 70,000 years ago that is still seen as a light echo in `Hanny's Voorwerp', but whose present-day radiative output is lower by at least 2 and more likely by over 4 orders of magnitude. This extremely rapid shutdown provides new insights into the physics of accretion in supermassive black holes, and may signal a transition of the accretion disk to a radiatively inefficient state.